Manejo agronómico del cultivo de granado (punica granatum l.) en Virú - La Libertad - Fernández Rodriguez, Jovi Valentin (2013)
The mam objective is to describe how to perform the agronomic management of pomegranate cultivation in the company Camposol S A, Viru - La Libertad. The crop requires good subsoiling and harrowing to achieve good root development. The most widely used propagation is the asexual cultivation using hardwood cuttings.Sowing was done at 6 x 5, with double density is thus obtained 666 plants 1 ha. Fertilization takes place with the experience ofthe company and farmers Camposol. The crop is irrigated using drip of 4000 m3 of water facility and also has sophisticated equipment fertigation. In the culture were presented the following weeds: purslane, redroot female, black nightshade and dairy which was controlled by hand weeding and herbicide use. In the culture was performed two pruning one in winter and one in summer, the latter being the most important. The most important phenological stages are swollen bud, bud initiation, bud sprouting and growth.For phytosanitary control pesticide applications are performed and biologicals that can be applied by machine or backpack lever.